Nietzsche’s Anti-Positivist Thought in His Middle Period - Langone, Laura (Sententiae, 2024)
In this paper, I aim to call into question a long-established tradition within the Anglo-Saxon Nietzsche scholarship that regards Nietzsche’s middle period as positivist. Unlike most scholars, I shall demonstrate that in Human, All Too Human Nietzsche does not take a positivist position, recognizing the limits of science with regard to knowledge of reality and its contributions toward unleashing human potential. Ultimately, I will show that Nietzsche was coherent, taking an anti-positivist position in all three works of the middle period.